Human papillomavirus detection and p16 methylation pattern in a case of esophageal papilloma - L.A. Afonso; N. Moysés; S.M.B. Cavalcanti (Brazilian Journal of Medical and Biological Research, 2010)
Esophageal cancer is a prevalent cancer worldwide. Some studies have reported the possible etiology of human papillomavirus (HPV) in benign and malignant papillomas of the esophagus but the conclusions are controversial. In the present study, we investigated an esophageal papilloma from a 30-year-old male patient presenting aphasia. HPV DNA was detected by generic PCR using MY09/11 primers, and restriction fragment length polymorphism revealed the presence of HPV54, usually associated with benign genital lesions. Hypermethylation of the pINK4A gene was also investigated due to its relation to malignant transformation, but no modification was detected in the host gene. Except for an incipient reflux, no risk factors such as cigarette smoking, alcohol abuse or an infected sexual partner were recorded. Since esophageal lesions may have a malignant potential, HPV detection and typing are useful tools for patient follow-up.